2012
DOI: 10.1002/eji.201142209
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Th1 and Th17 cells determines transition from autoimmune myocarditis to dilated cardiomyopathy

Abstract: Myocarditis is a potentially lethal inflammatory heart disease of children and young adults that frequently leads to dilated cardiomyopathy (DCM). Since diagnostic procedures and efficient therapies are lacking, it is important to characterize the critical immune effector pathways underlying the initial cardiac inflammation and the transition from myocarditis to DCM. We describe here a T-cell receptor (TCR) transgenic mouse model with spontaneously developing autoimmune myocarditis that progresses to lethal DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
103
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 52 publications
2
103
2
1
Order By: Relevance
“…The protective effect of IFN-γ observed in mice deficient in IFN-γ or its receptor [6,22] is thus likely to be due mainly to the facts that (i) IFN-γ confines activated CD4 + T-cell expansion via nitric oxide [34], (ii) IFN-γ is involved in regulating CD4 + T-cell activation and apoptosis [31], and (iii) IFN-γ suppresses exacerbating Th17 responses [41][42][43], and thus to be unrelated to the IFN-γ-induced MHCII expression addressed in our study. Remarkably, two reports applying distinct models of spontaneous EAM, which are not based on immunization with α-MyHC, proposed that IFN-γ is driving the initial inflammatory phase of EAM [19,20]. Our finding that neutralization of IFN-γ during the late acute phase of EAM (i.e.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The protective effect of IFN-γ observed in mice deficient in IFN-γ or its receptor [6,22] is thus likely to be due mainly to the facts that (i) IFN-γ confines activated CD4 + T-cell expansion via nitric oxide [34], (ii) IFN-γ is involved in regulating CD4 + T-cell activation and apoptosis [31], and (iii) IFN-γ suppresses exacerbating Th17 responses [41][42][43], and thus to be unrelated to the IFN-γ-induced MHCII expression addressed in our study. Remarkably, two reports applying distinct models of spontaneous EAM, which are not based on immunization with α-MyHC, proposed that IFN-γ is driving the initial inflammatory phase of EAM [19,20]. Our finding that neutralization of IFN-γ during the late acute phase of EAM (i.e.…”
Section: Discussionsupporting
confidence: 47%
“…On the one hand, IFN-γ exerts a protective role by limiting the expansion of autoreactive heart-specific CD4 + T cells. On the other hand, several observations point to a-not yet understood-disease promoting role for IFN-γ during myocarditis induction [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, it is widely accepted that the mainstay actor is the T-helper (Th)1 cell, crucially involved in orchestrating the immune response required for the defence of the virus-infected heart, but also responsible for the organ damage [4]. Nevertheless, increasing evidence strongly suggests that also interleukin (IL)-17 producing Th17 cells play a key role in the process, particularly in the progression of myocarditis to DCM [5,6].…”
mentioning
confidence: 99%
“…This effect may be of particular relevance in the clinical setting as increasing evidence indicates that although Th17 cells, and in particular IL-17A, have only a mild effect on the severity of myocarditis during the acute phase in which the major role seems to be played by the Th1 cell [2,4], however they are essential for the long-term progression to DCM [5,6]. In fact, it has been demonstrated that IL-17A-deficient mice, while developing myocarditis with similar incidence and severity to wild-type controls, were protected from postmyocarditis remodelling and did not develop DCM.…”
mentioning
confidence: 99%